Design, Development And Characterization Ofmucoadhesive Tablets Of Atenolol - YASH PAUL; SUNIL KUMAR; RAHUL SEHRAWAT (International Journal of Pharma and Bio Sciences, 2012)
The aim of the present study was to formulate mucoadhesive tablets of atenolol using different bioadhesive polymers. The tablets were prepared using Sodiumcarboxymethylcellulose, Carbopol 940 and Hydroxypropylmethylcellulose as bioadhesive polymers to impart Mucoadhesion. Tablets were evaluated by different parameters such as weight uniformity, drug content, thickness, hardness, surface pH, swelling index mucoadhesive strength, wash out time and in vitro drug release. No significant change was observed in physical appearance, drug content, surface pH, mucoadhesive strength, wash off time or in vitro dissolution pattern after storage at 45oC/75% RH for three months.